In quest of Babylonian Tannaitic traditions II: the case of Avuha de-Shmuel - Cohen, Barak S. (The journal of Jewish studies, 2015)
The article examines the nature and origin of legal traditions set down by Avuha de-Shmuel, a Nehardean sage from the end of the Parthian period. Topics discussed include the pre-Talmudic Babylonian halakhah; Palestinian halakhic influence on the traditions; and analysis of Babylonian Talmud, central text of Rabbinic Judaism.